Approaching Innovation - Stephen Kieran; James Timberlake (Oz, 2016)
Are we living in an Age of Innovation? The news of the day would have us believe so. As an experiment, we tracked the instances we encountered of the word “innovation” being used during the course of an ordinary weekday morning: an advertisement for a private school promises not just an innovative curriculum, but the teaching of innovation itself as a subject. A radio journalist interviews the new Vice Chair of Business Innovations at General Electric about the company’s global innovation barometer.